2017
DOI: 10.1021/acs.biochem.6b01101
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Patterns for Neighboring Bases Near the Stacked State in Nucleic Acid Strands

Abstract: Structural variation in base stacking has been analyzed frequently in isolated double helical contexts for nucleic acids, but not as often in nonhelical geometries or in complex biomolecular environments. In this study, conformations of two neighboring bases near their stacked state in any environment are comprehensively characterized for single-strand dinucleotide (SSD) nucleic acid crystal structure conformations. An ensemble clustering method is used to identify a reduced set of representative stacking geom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Analogous nearest-neighbour effects have been reported for very short oligoribonucleotides, e. g. GAA [40][41][42] and for a single-stranded hexadeoxyribonucleotide, d-AGGCCT, [6] where the hydrogen resonances on adenine and cytosine bases were shifted in response to the deprotonation (at pH around 10) of neighbouring thymine or guanine groups. Such results reflect the importance of stacking interactions between the bases [43,44] even in single-stranded nucleic acids.…”
Section: Titration Behaviour Of the Pseudoaromatic-h Resonances In D-...mentioning
confidence: 72%
“…Analogous nearest-neighbour effects have been reported for very short oligoribonucleotides, e. g. GAA [40][41][42] and for a single-stranded hexadeoxyribonucleotide, d-AGGCCT, [6] where the hydrogen resonances on adenine and cytosine bases were shifted in response to the deprotonation (at pH around 10) of neighbouring thymine or guanine groups. Such results reflect the importance of stacking interactions between the bases [43,44] even in single-stranded nucleic acids.…”
Section: Titration Behaviour Of the Pseudoaromatic-h Resonances In D-...mentioning
confidence: 72%
“…Interestingly, various thymine dinucleotide stacking geometries have been identified in single-stranded regions of nucleic acid crystal structures. 34,35 Our results are likely to be useful to identify staked state candidates as proreactive species based on their sugar pucker combination.…”
Section: Discussionmentioning
confidence: 94%
“…We showed that RNA SSDs approach a B-form structure in many instances, 3 and this local B-form structure seems to be achieved through both C2 -endo sugar conformations or base stacking patterns that resemble B-form DNA stacking. 4 Interestingly, the base RMSD values show a greater propensity for B-form structures than the sugar-phosphate backbone at the SSD level, which suggests an under-representation of B-form-like sugar-phosphate conformations for RNA in the PDB models. While duplex RNA usually adopts an A-form structure with its furanose sugars assuming C3 -endo pucker conformations, 5 the C2 -endo pucker is present in some functional RNA motifs, and may possibly be implicated in RNA folding.…”
mentioning
confidence: 98%